PERLINDUNGAN HUKUM TERHADAP ANAK BUAH KAPAL (ABK) INDONESIA YANG BEKERJA DAN MENGALAMI PERBUDAKAN MODERN (MODERN SLAVERY) DI KAPAL PERIKANAN ASING - Dorma Hotmaria Sianipar; Maria Maya Lestari; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesian sailors generally work as fishermen on foreign vessels. Fishing is themost dangerous, dirty and difficult job in the world. About 15 million are involved in marinefishing. The practice of violating human rights in the form of modern slavery often occursand is experienced by crew members on foreign fishing vessels. In this case, in 2020Indonesian crew members worked on Chinese ships. In detail, there are 46 Indonesian crewmembers working on the ship. Cases experienced by Indonesian crew members includeunpaid salaries, threats and intimidation during work, inappropriate working conditions,physical violence or inhumane treatment or violations of human rights. Preventive efforts from Indonesia can be carried out by supervising the manningagency as a company for placing ABK on Chinese ships by strengthening institutionalstrengthening, which can be done by affirming the authority to issue permits for companiesto recruit and place crew members by the Ministry of Manpower and BP2MI through theGovernment Regulation on the Placement and Protection of Crews on Fishing Vessels. . Therepressive efforts are by pursuing diplomatic and consular efforts as well as ratification ofthe ILO Number 188 of 2007 concerning Work in Fishing and ratifying the convention thatregulates the protection of crew related to ship safety (CTA 2012). This type of research is normative legal research using research methods on legalprinciples, namely the principle of passive nationality. The data collection technique in thisresearch is literature study, reviewing, analyzing and analyzing the data qualitatively anddrawing conclusions deductively. From the results of the research problem, there are threemain things that can be concluded. First, the regulation of international legal protection forIndonesian crew members who work and experience modern slavery on foreign fishingvessels, namely preventive legal protection and repressive legal protection. Second, theregulation of international legal protection for Indonesian crew members who work andexperience modern slavery on foreign fishing vessels. Third, the problems faced by thegovernment with assistance through the role of state institutions in providing legalprotection to Indonesian crew members who work and experience modern slavery on foreignfishing vessels.Keywords: Legal Protection, Ship's Crew (ABK), Modern Slavery, Foreign FishingVessels